Thermophysical performances of Sm2O3-doped Gd3TaO7 oxides for thermal barrier coatings. Issue 8 (July 2023) - Sang, Weiwei; Zhang, Hongsong; Liu, Shuaixia; Zhang, Haoming; Ren, Bo; Tang, An; Chen, Xiaoge; Xie, Wenbo; Hou, Ruiyi; Ma, Hongjun; Li, Siqi
Abstract: To investigate the effect of Sm3 O3 addition on the thermophysical performances of Gd3 TaO7, (Gd1−x Smx )3 TaO7 oxides were synthesised using sol-gel and sintering with high-temperature technologies, and their thermophysical properties were researched. The investigations exhibit that the obtained powders comprise well-distributed particles, and the bulk specimens have densified microstructures. The obtained ceramics have single pyrochlore-lattice. Owing to varied scattering strength coefficient of phonon caused by the differences in ionic radius and mass between the substituting and substituted elements, the value of thermal conductivity of (Gd1−x Smx )3 TaO7 decreases firstly and further increases with the increase fraction of Sm2 O3 . The coefficient of thermal expansion of (Gd1−x Smx )3 TaO7 is ameliorated owing to the higher ionic radius of Sm 3+ than Gd 3+ . Except for Sm3 TaO7, the synthesised ceramics display outstanding lattice steadiness up to 1400 °C. Highlights: The (Gd1−x Smx )3 TaO7 oxides were prepared by a modified sol-gel technique and high-temperature sintering method. The obtained oxides have single pyrochlore-type lattice, and no element is lost during high-temperature calcination. The (Gd1−x Smx )3 TaO7 oxides have low thermal conductivity and high expansion coefficient. Except for Sm3 TaO7, the obtained oxides are of excellent phase-stability up to 1400 °C. The (Gd1−x Smx )3 TaO7 oxides can be used as candidate for thermal barrier coatings.